Design of plantwide control and safety analysis for diethyl oxalate production via regeneration-coupling circulation by dynamic simulation. (2nd February 2019) - Zhu, Jiaxing; Hao, Lin; Bai, Wenshuai; Zhang, Bo; Pan, Bochen; Wei, Hongyuan
Highlights: Several control structure are proposed and evaluated based on selected control performance criteria. An effective control structure using a feed-forward ratio with composition controller for this process is determined. Model-based HAZOP is conducted for safety analysis and hazard identification by integration of dynamic simulation and HAZOP. A quantitative variables trend and change rate due to quantitative deviations is obtained through dynamic simulation. A general procedure based on simulation for design and safety analysis of chemical process is proposed. Abstract: In this article, the plantwide control of a novel process for diethyl oxalate production via two steps is investigated. The unique feature of this process is that there is a closed regeneration-coupling circulation. It results in that two steps should be matched properly and mass balance for overall reaction should be satisfied precisely. An effective control structure using a feedforward ratio with composition controller is determined. Later, safety analysis for this process is investigated by the integration of dynamic simulation and HAZOP (hazard and operability analysis). In comparison with heuristic HAZOP, quantitative deviations can be introduced. Quantitative variation trends and change rates of important variables can be determined. Determining increase rate in temperature and pressure is significantly important, since response time as indirect indictor can be used to assess the possibility of risk. Finally, a general procedure based on simulation for design and safety analysis of chemical process is proposed.